Insurance coverage policies for infertility services in health insurance: a systematic review of global practices and disparities - Seyed Ahmad Ahmadi; Sajad Moeini; Ensieh Ketabchi; Mohammad Veysi Sheikhrobat; Monireh Shamsaei (Gynecology and Obstetrics Clinical Medicine)
Background Infertility affects about 10% of the global population, imposing significant economic and psychosocial burdens. This systematic review examines disparities in insurance coverage for infertility services worldwide, assessing how these disparities affect access to care and fertility outcomes.Methods For this systematic review, scientific databases (PubMed, EMBASE, Web of Science and Scopus) were searched from the beginning of 1990 to 2022 to identify literature related to insurance coverage for infertility services by health insurance organisations worldwide. Two researchers screened titles and abstracts, extracted data from full-text articles and assessed their quality using the Joanna Briggs Institute Critical Appraisal Tool.Results 11 studies, primarily from high-income countries, met the inclusion criteria. Findings show a substantial increase in access to infertility services in countries with comprehensive insurance policies, such as the USA, where Medicaid coverage led to a 27% increase in first births among women over 35 years. Disparities in coverage, particularly in advanced treatments such as assisted reproductive technology and in vitro fertilisation (IVF), were notable, with limited coverage in countries such as Japan. Low-income countries generally lack sufficient insurance policies, exacerbating access disparities.Conclusion Insurance coverage policies for infertility services are associated with improved fertility outcomes, especially through increased access to infertility services. However, coverage disparities remain, emphasising the need for comprehensive policies to reduce economic barriers and support equitable access across regions.